Implementasi Client Centered Theraphy Sebagai Asistensi Perilaku Negatif Siswa - Ikke Nurjanah Sinaga; Nurjannah Nurjannah (Institut Agama Islam Negeri Curup, 2022)
This article aims to describe the implementation of the client centered therapy approach as an effort to assist students in the negative behavior of students in one of the Islamic boarding schools in the city of Kisaran. This research is motivated by the many negative behaviors carried out by students in schools such as violating various school rules and regulations, fighting teachers, etc. This research uses descriptive qualitative method with case study type. The data analysis technique is done by reducing the data, presenting the data and drawing conclusions. Meanwhile, the data validity technique uses the credibility test with the type of triangulation. The results showed that: 1) forms of negative behavior carried out by students were truancy, lying sick so as not to participate in learning in class, violating school rules such as leaving the boarding school environment without the knowledge and permission of the ustadz or cleric in the dormitory, bringing communication tools such as (mobile phones) into the dormitory, fighting with friends, dating in the school environment and fighting with the teacher, there are 2 trigger factors for students to behave negatively, namely internal factors and external factors, 3) based on the results of observations stated that client centered therapy is said to be enough to provide good changes to changes in students' negative behavior. Based on this, the researcher recommends the counseling guidance teachers to collaborate with client centered therapy techniques with other counseling approaches so that it will be more possible for the success of the counseling process to be carried out.